Infrared Spectroscopic Study of the Acidic Character of Modified Alumina Surfaces - Aline Auroux; Antonella Gervasini (Adsorption Science & Technology)
The infrared spectra of the hydroxyl region and of the regions associated with chemisorbed CO 2 and pyridine species on pure and modified aluminas loaded with various amounts of Li + or SO 2- 4 ions were investigated. It was found that, following treatment with lithium acetate or ammonium sulphate, the same –OH groups were involved in both modifications, acting in turn as acidic –OH groups capable of exchanging their protons with lithium ions or as basic groups capable of exchanging with acid sulphate anions or acting as strong nucleophiles to form hydrogen carbonates with carbon dioxide. Modified alumina experienced a general weakening of its initial Lewis acid centres on loading with Li + ions. These ions did not act as new Lewis-type acid centres even on high loading. Under these circumstances, in addition to lithium aluminate, they might generate a lithium oxide-type layer or clusters capable of behaving as new basic species forming lithium carbonates upon adsorption of CO 2 . Sulphated alumina showed a Brönsted-type acidity presumably due to Al–O–SO 3 H groups that were detected via the S=O (but not S–OH) absorption frequencies. The basic properties of the parent material were totally suppressed by sulphation.